Biological characteristics associated with virulence in Clostridioides difficile ribotype 002 in Hong Kong - Ka Yi Kong; Thomas N. Y. Kwong; Hung Chan; Kristine Wong; Samuel S. Y. Wong; Anu P. Chaparala; Raphael C. Y. Chan; Lin Zhang; Joseph J. Y. Sung; Jun Yu; Peter M. Hawkey; Margaret Ip; et al. (Taylor & Francis, 2020)
Clostridioides difficile infection (CDI) is a common cause of nosocomial diarrhea and can sometimes lead to pseudo-membranous colitis and toxic megacolon. We previously reported that the PCR ribotype 002 was a common C. difficile ribotype in Hong Kong that was associated with increased mortality. In this study, we assessed in vitro bacteriological characteristics and in vivo virulence of ribotype 002 compared to other common ribotypes, including ribotypes 012, 014 and 046. We observed significantly higher toxin A (p < 0.05) and toxin B (p < 0.05) production, sporulation (p < 0.001) and germination rates (p < 0.0001) in ribotype 002 than other common ribotypes. In a murine model of C. difficile infection, ribotype 002 caused significantly more weight loss (p < 0.001) and histological damage (p < 0.001) than other common ribotypes. These findings may have contributed to the higher prevalence and mortality observed, and provided mechanistic insights that can help public surveillance and develop novel therapeutics to combat against this infection.
Keywords: Medicine; Microbiology; Sociology; Biological Sciences not elsewhere classified; Information Systems not elsewhere classified; Mathematical Sciences not elsewhere classified; Cancer; Infectious Diseases; Virology